2018
DOI: 10.1186/s13002-018-0227-6
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotany of the Sierra Nevada del Cocuy-Güicán: climate change and conservation strategies in the Colombian Andes

Abstract: BackgroundThe Sierra Nevada del Cocuy-Güicán in the Colombian Andes is protected as a National Natural Park since 1977 because of its fragile páramo ecosystems, extraordinary biodiversity, high plant endemism, and function as water reservoir. The vegetation on this mountain is threatened by expanding agriculture, deforestation, tourism, and climate change. We present an ethnobotanical inventory among local farmer communities and discuss the effects of vegetation change on the availability of useful plants.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 30 publications
(43 reference statements)
0
14
0
4
Order By: Relevance
“…In North America, the extinction risk for a population of American ginseng of median size over 70 years was estimated to be 8 % over 70 years with harvesting alone, 6 % with climate change alone, but 65 % with the two combined [28]. Inhabitants of the Colombian Andes reported that the herb Draba litamo L. Uribe, endemic to the high-altitude páramo vegetation and a revitalizing tonic traditionally claimed to convey eternal youth, was increasingly scarce due to the combination of climate change and commercial harvesting [79]. In Africa, Pterocarpus angolensis DC.…”
Section: Decreased Availability and Extinction Of Populationsmentioning
confidence: 99%
“…In North America, the extinction risk for a population of American ginseng of median size over 70 years was estimated to be 8 % over 70 years with harvesting alone, 6 % with climate change alone, but 65 % with the two combined [28]. Inhabitants of the Colombian Andes reported that the herb Draba litamo L. Uribe, endemic to the high-altitude páramo vegetation and a revitalizing tonic traditionally claimed to convey eternal youth, was increasingly scarce due to the combination of climate change and commercial harvesting [79]. In Africa, Pterocarpus angolensis DC.…”
Section: Decreased Availability and Extinction Of Populationsmentioning
confidence: 99%
“…The tropics may be at higher risk due to their expected higher turnover in climatic conditions, and their extremely high concentration of endemic plant species, narrowlydistributed human cultures, and therefore plant uses (Pironon et al, in review). Some of the detrimental effects of climate change on useful plants have already been perceived by local communities, such as in the Sierra Nevada del Cocuy-Güicán of Colombia, where climate change, together with unsustainable land use and overharvesting are causing a decline in medicinal plant resources (Rodríguez, Angueyra, Cleef, & Van Andel, 2018). Moreover, narrow-ranged species and tropical areas might be even more vulnerable because they are also expected to be particularly impacted by other global change drivers such as land use change or biotic invasions.…”
Section: The Impact Of Range Raritymentioning
confidence: 99%
“…For the majority of useful plants that are not cultivated, cultural choices are crucial to enable conservation of wild populations. Conservation may also be key to enabling discovery of currently unknown or undocumented useful plants (Dempewolf et al, 2014;Garnett et al, 2018;Rodríguez et al, 2018). In the medium-term, plant breeding and genomic prediction tools are likely to enable faster development of resilience traits (for example; breeding of dieback resilient Fraxinus in the UK).…”
Section: Human Influence On Plant Resiliencementioning
confidence: 99%
“…Estos datos coinciden con los estudios realizados por Galvis y Torres (2017) en comunidades rurales de Sogamoso; y de Rodríguez et al (2018) en el ecosistema de páramo en la Sierra Nevada del Cocuy, donde la Asteraceae es la familia más importante, debido al uso medicinal que se da por parte de la comunidad, lo cual demuestra la relevancia de esta familia para las comunidades rurales que habitan las zonas de amortiguación del páramo. Igualmente, en cuanto a la representatividad por género, se destacan Diplostephium, Hypericum y Miconia, situación que coincide con el patrón de riqueza de este ecosistema…”
Section: Caracterización Florísticaunclassified
“…Sobre esta problemática se han realizado estudios desde la etnobotánica en las zonas de páramo de Colombia, tales como los desarrollados por Pérez y Matiz-Guerra (2017), en comunidades campesinas de Bogotá, y los de Rodríguez et al (2018), llevado a cabo en la Sierra Nevada del Cocuy; ambos con la intención de registrar el conocimiento tradicional relacionado con la vegetación de esas áreas.…”
Section: Introductionunclassified